Pengembangan Komik Ecopet (E-Comic Calon Pemimpin Teladan) sebagai Media dalam Mengenalkan Politik Islam pada Siswa Kelas VI SD - Gunadi, Radila Putri; Zulaikha, Zulaikha; Nugraha, Fauzan Ramdhan; Aeni, Ani Nur (FONDATIA, 2023)
A leader elected by the people should be able to prosper the people and bring security and peace within a country. In fact, there are many figures of Indonesian leaders who have overshadowed their power to make the people miserable. The figure of such a leader should not be imitated because it disregards the values of a leader from the perspective of Islam. Therefore, political education should be given to the younger generation of elementary school students in order to form a young generation that understands the political values in Islam and how to apply them in everyday life, as well as equip the young generation as a successor to become a leader. The research is aimed at providing political learning from the perspective of Islam through comic-style learning media. This e-comic contains the stories of the leadership of the Prophet Muhammad's friends after the death of Muhammad SAW. In the story of the friends of the prophet many values of leadership in the perspective of Islam that can be enlightened by the young generation. Research Methods Using Design and Development Methods (D&D) The results of the research showed that the development of comics ECOPET (E-Comic Candidate Model Trimmer) produced a good response from students and teachers, so that e-comic was effectively applied to students in grade 6th. Through e-comics helps students to understand the attitude and character of a good leader in an Islamic perspective.